2007
DOI: 10.1074/jbc.m611455200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mechanistic Analyses of endo-Glycoceramidase II, a Membrane-associated Family 5 Glycosidase in the Apo and GM3 Ganglioside-bound Forms

Abstract: endo-Glycoceramidase, a membrane-associated family 5 glycosidase, deviates from the typical polysaccharide substrate specificity of other soluble members of the family, preferentially hydrolyzing glycosidic linkages between the oligosaccharide and ceramide moieties of gangliosides. Here we report the first x-ray crystal structures of an endo-glycoceramidase from Rhodococcus sp., in the apo form, in complex with the ganglioside G M3 (Svennerholm ganglioside nomenclature (Svennerholm, L. (1964) J. Lipid Res. 5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 65 publications
3
46
0
Order By: Relevance
“…That is, a fl exible loop hanging over the catalytic cleft is present in EGCase II but not EGCase I. The complex structure of EGCase II with GM3 (NeuAc ␣ 2-3 Gal ␤ 1-4Glc ␤ -Cer) revealed that the 4-hydroxyl group of the internal ␤ -galactose in GM3 is located close to the loop ( 17 ). On the other hand, the 4-hydroxyl group is substituted with ␣ -galactose in globo-series GSLs such as Gb3Cer (Gal ␣ 1-4Gal ␤ 1-4Glc ␤ -Cer), suggesting that the presence of a loop could affect the turnover of substrates and products in the catalytic region.…”
Section: Mechanical Insights Into the Difference In Reaction Effi Ciementioning
confidence: 99%
See 3 more Smart Citations
“…That is, a fl exible loop hanging over the catalytic cleft is present in EGCase II but not EGCase I. The complex structure of EGCase II with GM3 (NeuAc ␣ 2-3 Gal ␤ 1-4Glc ␤ -Cer) revealed that the 4-hydroxyl group of the internal ␤ -galactose in GM3 is located close to the loop ( 17 ). On the other hand, the 4-hydroxyl group is substituted with ␣ -galactose in globo-series GSLs such as Gb3Cer (Gal ␣ 1-4Gal ␤ 1-4Glc ␤ -Cer), suggesting that the presence of a loop could affect the turnover of substrates and products in the catalytic region.…”
Section: Mechanical Insights Into the Difference In Reaction Effi Ciementioning
confidence: 99%
“…The model showed a ( ␤ / ␣ ) 8 barrel structure typical for GH family 5 glycosidase. The crystal structure of EGCase II shows a highly disordered and fl exible loop region (Pro 145 to Gly 154 ) hanging over the active site ( 17 ). This region was absent in EGCase I ( Fig.…”
Section: Substrate Specifi City Of the Recombinant Egcase Imentioning
confidence: 99%
See 2 more Smart Citations
“…GH9 family enzymes have an (␣/␣) 6 -barrel fold, and this family of enzymes is known to contain members that exhibit different enzymatic activities, including endoglucanase (45), cellobiohydrolase (15), 1,4-␤-D-glucan glucohydrolase (43), ␤-glucosidase (40), and exo-␤-glucosaminidase (23). The GH5 family of enzymes have an (␤/␣) 8 -barrel fold, and this family also encodes diverse enzymatic activities, including endoglucanase (16), mannanase (20), mannosidase (20), xylanase (14), chitosanase (50), glucosidase (11), licheninase (25), fucosidase (61), galactanase (44), endoglycoceramidase (9), and mannan transglycosylase (6). The binding cleft in GH9 catalytic modules can hold six sugar molecules, among which four subsites (Ϫ4 to Ϫ1) are at the nonreducing end and the two remaining subsites are at the reducing end (ϩ1 to ϩ2) (45).…”
mentioning
confidence: 99%